Euphorbia heterophylla leaves as herbal tea: An ethno-scientific approach to boosting scientific literacy - Dyah Ayu Fajarianingtyas; Jefri Nur Hidayat; Aryo Wibisono; Izzah Afkarina (Biosfer: Jurnal Pendidikan Biologi, 2025)
The urgency of the research is to produce a poster product of Patik Sir leaf tea (Euphorbia heterophylla) on the diffusion material to improve scientific literacy skills. The phenomenon that occurs in class IX students is the lack of student involvement in practical science activities so that scientific literacy abilities also decrease. The main objective of this research is to produce posters as supporting media for practical science learning. The development of this poster took an ethnoscience approach using the object of Patik Sir (Euphorbia heterophylla) leaf tea. The research method uses Research and Development (R&D) based on the Borg & Gall. The research subjects were 28 class IX students of SMAN 1 Lenteng, Indonesia. Research instruments include validation sheets, scientific literacy description tests, and questionnaires. The data analysis technique uses a percentage formula to analyze validity and response data. Scientific literacy data was analyzed using n-gain score and paired sample t test. The results of the study showed that poster products were very effective for application in science learning so that science literacy increased. The results of this research provide a contribution that the potential of the wild plant Patik Sir (Euphorbia heterophylla) can be used as a reference for science learning materials.